A Preliminary study of insects associated with some Weeds in El-Beida region in Libya - Amin, A. H.; Bataw, A. A.; El-Ghariani, I. M. (Al-Mukhtar Journal of Sciences, 1998)
A survey of insects associated with weeds was conducted in El- Beida region in Libya during the period from 1995 to 1997. The results showed that, thirty-eight species of insects belong to twenty-five families from seven orders were recorded associated with twenty species of weeds belong to ten families. The interactions between weeds and insects were also investigated. Many weed plants considered as primary hosts for insect pests, other weeds offer pollen and nectar to some insects. Some insects were found to have a role in controlling weeds biologically.